Upaya Meningkatkan Kemampuan Menggiring Bola Dalam Permainan Sepak Bola Melalui Pembelajaran Kelincahan Murid Kelas VI MIN 2 Makassar - Muhammad Hasbillah; Sarifuddin Arham; Abdullah Ilyas (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2021)
The study aimed at describing the planning, performance, observation, reflection, and the implementation of agility learning in improving agility ability in football of class VI Madrasah Ibtidaiyah Negeri 2 Makassar. The study is a classroom action research conducted in four meetings in cycle I and cycle II. The study was designed in four phases, namely the planning, the implementation, the observation, and the reflection. Data of the study was basic ability of dribbling the ball as psychomotor data. The data sources were 26 students of class VI in Madrasah Ibtidaiyah Negeri 2 Makassar. Data collection of dribbling ability used assessment sheet of initial attitude technique, body position, feet movement, and final attitude, as well as multiple choice assesment sheet in cycle I and cycle II. Data were then analyzed quantitatively. The result of quantitative data analysis revealed that 15 students completed in cycle I with 57,70% and 24 students completed in cycle II with 92,30%. The conclusion of the study was Penjasorkes learning through agility learning method in football dribbling could improve dribbling ability of class VI students in Madrasah Ibtidaiyah Negeri 2 Makassar.